2015
DOI: 10.5489/cuaj.2626
|View full text |Cite
|
Sign up to set email alerts
|

A guidewire introducer as a ureteral foreign body: A case report

Abstract: A 63-year-old male, previously treated for a ureteral tumour by a right-sided segmental ureterectomy and end-to-end anastomosis of ureteral segments, was referred to our clinic for endoscopic follow-up. During his follow-up, he was diagnosed with partial right-sided ureteral stricture which eventually progressed to complete obstruction. During the ureteroscopy, as the stenotic segment did not allow passage of an hydrophilic guidewire, an antegraderetrograde approach was decided. On the antegrade endoscopic vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…2,3 Guidewire introducer in the right proximal ureter, suprapubic catheter in the left distal ureter, embolization coil and endoscopic glue material both in the proximal ureter were revealed in 4 case studies. 1,4,6,9 The proximal ureter was the commonest site for foreign body in the review 42% (6/14) as most of the precipitating factors or previous procedures were in the vicinity of the proximal ureter and kidney. The mean indwelling time of the foreign body in the ureters was 4.3 years as Shuaibin et al reported the least duration of 12 days with a suprapubic catheter dislodged in the left distal ureters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3 Guidewire introducer in the right proximal ureter, suprapubic catheter in the left distal ureter, embolization coil and endoscopic glue material both in the proximal ureter were revealed in 4 case studies. 1,4,6,9 The proximal ureter was the commonest site for foreign body in the review 42% (6/14) as most of the precipitating factors or previous procedures were in the vicinity of the proximal ureter and kidney. The mean indwelling time of the foreign body in the ureters was 4.3 years as Shuaibin et al reported the least duration of 12 days with a suprapubic catheter dislodged in the left distal ureters.…”
Section: Resultsmentioning
confidence: 99%
“…Other symptoms reported were flank pain, 3-5,10,11 followed by dysuria, 2,5,8,12 along with two incidental findings from imaging. 1,13 A total of 10/14 of the case reports, (Figure 3 and 4) 2,5-10,13 highlighted ureteroscopy + holmium laser fragmentation of calcification along with grasping forceps for retraction of foreign body . Li et al reported a laparoscopic left nephroureterectomy for a nonfunctioning kidney after lodging an intrauterine contraceptive device in the left distal ureter for 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sonrasında üreteropelvik bölgede gelişen 1 cm çapındaki taşın nedeninin, migrate olan zamk maddesinin olduğu belirlenmiştir (8). Diğer bir yayında segmental üreter rezeksiyonu ve uç uca üreter anastomozu yapılan bir hastanın, sonrasında gelişen üreter stenozunun nedeninin operasyon sırasında kullanılan ve unutulan "kılavuz tel introduser" olduğu bildirilmiştir (9). Üriner sisteme yapılan müdahaleler dışında, özellikle abdominal ve kadın doğum cerrahisi geçiren hastalarda da benzer durumlar görülebilmektedir.…”
Section: Discussionunclassified